2016
DOI: 10.1136/heartjnl-2015-309230
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of cardiac rehabilitation after balloon pulmonary angioplasty for chronic thromboembolic pulmonary hypertension

Abstract: ObjectiveTo determine safety and efficacy of cardiac rehabilitation (CR) initiated immediately following balloon pulmonary angioplasty (BPA) in patients with inoperable chronic thromboembolic pulmonary hypertension (CTEPH) who presented with continuing exercise intolerance and symptoms on effort even after a course of BPA; 2–8 sessions/patient.MethodsForty-one consecutive patients with inoperable CTEPH who underwent their final BPA with improved resting mean pulmonary arterial pressure of 24.7±5.5 mm Hg and wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 28 publications
(44 reference statements)
2
55
0
Order By: Relevance
“…Exercise training can lead to meaningful improvements in exercise capacity, muscular function, QoL and possibly right ventricular function and pulmonary haemodynamics [3]. Beneficial effects of exercise training have been shown in six randomised controlled trials [15,[22][23][24][25][26], three controlled trials [27][28][29], 10 prospective cohort studies [16][17][18][19][20][21][30][31][32][33][34][35], three case series [34][35][36], two retrospective cohort studies [37,38] and four meta-analyses [39][40][41] including one Cochrane review [42]. Beside the clinical effects, it has also been shown that exercise training may reduce inflammation and cell proliferation on a molecular level and may have a beneficial effect on the pulmonary vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise training can lead to meaningful improvements in exercise capacity, muscular function, QoL and possibly right ventricular function and pulmonary haemodynamics [3]. Beneficial effects of exercise training have been shown in six randomised controlled trials [15,[22][23][24][25][26], three controlled trials [27][28][29], 10 prospective cohort studies [16][17][18][19][20][21][30][31][32][33][34][35], three case series [34][35][36], two retrospective cohort studies [37,38] and four meta-analyses [39][40][41] including one Cochrane review [42]. Beside the clinical effects, it has also been shown that exercise training may reduce inflammation and cell proliferation on a molecular level and may have a beneficial effect on the pulmonary vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary hypertension is a cause of reduced exercise capacity; it may precede overt manifest pulmonary hypertension and is associated with a decreased life expectancy [28]. However, exercise training has been shown to be safe in these patients [11][12][13][14][15][16][29][30][31], and European guidelines recommend its use in experienced centers for patients who are clinically stable, on optimal pharmacological treatment [17,19].…”
Section: Discussionmentioning
confidence: 99%
“…In the past, exercise was not recommended in patients with pulmonary artery hypertension, particularly in those with more advanced disease due to safety concerns [17]. Pulmonary hypertension is a cause of reduced exercise capacity; it may precede overt manifest pulmonary hypertension and is associated with a decreased life expectancy [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Fukui et al reported the efficacy of cardiac rehabilitation after BPA for CTEPH. 16 Importantly, the study rehabilitation protocol was initiated immediately after the final BPA. Moreover, no patient experienced adverse events or deterioration of right-sided heart failure or hemodynamics, as confirmed with catheterization.…”
Section: Pulmonary Rehabilitation In Patients With Phmentioning
confidence: 99%